DEVELOPING STUDENTS PRODUCTIVE SKILLS WITH PROBLEM SOLVING APPROACH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Problem solving is not only a great way to apply language skills, but is one of the key elements in the list of thinking skills and learning competency. When students examine a difficult situation in order to identify both the problem and a meaningful solution, they are learning skills that will serve them well in the workplace, in their communities, at home with their families, and in their daily lives.